Hereditary tubulopathies including the associated bone disease - M. O. Ryznychuk; T. V. Khmara; M. I. Kryvchanska; I. I. Zamorskii (Regulatory Mechanisms in Biosystems, 2018)
Tubulopathy is a heterogeneous group of diseases combined by the nephron functions disorders of one or more enzyme proteins in the tubular epithelium that cease to function as a reabsorption of one or several substances filtered from the blood through the glomeruli into tubules, which determines the development of the disease. This review addresses the tubulopathies accompanying bone disease, namely: de Tony-Debre-Fanconi syndrome (autosomal dominant, autosomal recessive, X-linked), renal distal metabolic acidosis type I (classic, autosomal dominant, autosomal recessive inheritance), renal distal tubular metabolic acidosis I (autosomal dominant, autosomal recessive inheritance) and type II (autosomal recessive inheritance accompanying delayed mental development and eye disorders), combined distal and proximal renal tubular metabolic acidosis type III (autosomal recessive inheritance characterized by osteoporosis), hypophosphatemia rickets (X-linked dominant, autosomal dominant, primary hypercalciuria, autosomal recessive inheritance). However, the diagnosis of tubulopathy remains complex and requires expensive laboratory equipment and specialist expertise; it can be diagnosed in children showing the following symptoms: impaired growth, vitamin D resistant rickets (lower limb deformities between 2 and 3 years of age). In the evaluation of such patients urine analysis is commonly used (levels of calcium, phosphorus, pH, bicarbonate, sodium, potassium, glucose, creatinine, protein, amino acids), blood count (levels of creatinine, uric acid, alkaline phosphatase, glucose, pH and sodium, bicarbonate, potassium, chloride, calcium, phosphorus ions), ultrasound of the kidneys to detect nephrocalcinosis. Determination of serum parathyroid hormone concentration, vitamin D metabolites, aldosterone and plasma renin activity, cysteine lymphocyte concentration (suspicion to diagnose cystinosis) and ophthalmologist examination may also be used as additional diagnostic methods. Despite the fact that most tubulopathies can be diagnosed clinically, molecular genetic studies are needed to clarify the type of inheritance and prognosis. The use of calcitriol will help in the management of phosphorous levels in the blood. Correction of vitamin D deficiency state is not required. Calcitriol supplementation may prevent secondary hyperparathyroidism resulting from increased phosphate intake.